Technical Approach to Laparoscopic Examination of the Small Bowel in Gallstone Ileus. (12th October 2020) - Assali, Sarah; Mourany, John; Jones, Brendan; Dudas, Lauren; Szoka, Nova
Abstract : Background . Gallstone ileus is an infrequent cause of small bowel obstructions (SBO), accounting for only 0.1-5% of SBOs and 25% of nonstrangulating causes of SBO in the elderly population. There is scant literature available regarding the use of laparoscopy to treat gallstone ileus. Currently, much of the literature available is limited to case reports only. Methods . A complete laparoscopic approach was utilized to manage a 65-year-old woman with morbid obesity who presented with gallstone ileus. With regard to our technical approach, we describe the technical approach that facilitates safe laparoscopic examination of the entire small bowel and can be applied to other acute care surgery cases involving small bowel pathology. Results . The patient's postoperative course was complicated by new-onset atrial fibrillation which was treated medically with good response. She was safely discharged on postoperative day 2. Conclusion . Laparoscopy is a feasible option for the management of gallstone ileus and can lead to decreased morbidity compared to laparotomy. The technique described allows for laparoscopic examination of the entire small bowel.